2016
DOI: 10.18632/oncotarget.12863
|View full text |Cite
|
Sign up to set email alerts
|

The long noncoding RNA HOXA11 antisense induces tumor progression and stemness maintenance in cervical cancer

Abstract: Recent research has focused on the impact of long noncoding RNA (lncRNA) in cervical carcinogenesis. However, whether HOXA11 antisense (HOXA11-AS) is involved in cervical cancer remains to be elucidated. In the present study, we examined HOXA11-AS expression levels in cervical cancer patients and determined the relationships between HOXA11-AS expression and clinicopathological factors. We also investigated the bio-functional consequences of HOXA11-AS overexpression both in vitro and in vivo. HOXA11-AS expressi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
70
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 80 publications
(72 citation statements)
references
References 38 publications
(47 reference statements)
2
70
0
Order By: Relevance
“…There are also many types of lncRNAs that have been studied. Growing evidence suggests that lncRNAs are closely related with tumor . For example, lncRNA H19 promotes breast cancer progression, and plasma circulating lncRNA H19 can also serve as a screening and diagnostic marker for early breast cancer .…”
Section: Discussionmentioning
confidence: 99%
“…There are also many types of lncRNAs that have been studied. Growing evidence suggests that lncRNAs are closely related with tumor . For example, lncRNA H19 promotes breast cancer progression, and plasma circulating lncRNA H19 can also serve as a screening and diagnostic marker for early breast cancer .…”
Section: Discussionmentioning
confidence: 99%
“…EMT is characterized by lack of intercellular contacts, increasing components of the contractile cytoskeleton . Previous study has documented that EMT plays imperative roles in driving the initiation of malignant tumor invasion and metastasis . One of the important features of EMT is the loss of epithelial proteins such as E‐cadherin and enhanced expression of nonepithelial markers such as N‐cadherin and Vimentin.…”
Section: Discussionmentioning
confidence: 99%
“…CAN-17-2356 promote lymphangiogenesis and distant metastasis of cancer by interacting with RNA, DNA, or proteins [14,15]. In recent years, the expression of certain lncRNAs has been frequently reported to be functionally important for cervical cancer, including lincRNA-p21 [16], HOXA11-AS [17], HOTAIR [18] and ANRIL [19]. In our previous study, we identified a lncRNA termed LNMICC (lncRNA associated with LN metastasis in cervical cancer) (GenBank: HG501394.1, ENST00000518880.1) that is upregulated in cervical cancer tissues with LN metastasis compared to its expression in those without LN metastasis [20].…”
Section: Introductionmentioning
confidence: 99%